BrevicidineB, a New Member of the Brevicidine Family, Displays an Extended Target Specificity - Zhao, Xinghong; Kuipers, Oscar P. (Frontiers in Microbiology, 2021)
The group of bacterial non-ribosomally produced peptides (NRPs) has formed a rich source for drug development. Brevicidine, a bacterial non-ribosomally produced cyclic lipopeptide, displays selective antimicrobial activity against Gram-negative pathogens. Here, we show that brevicidineB, which contains a single substitution (Tyr2 to Phe2) in the amino acid sequence of the linear part of brevicidine, has a broadened antimicrobial spectrum, showing bactericidal activity against both Gram-negative and Gram-positive pathogens. Compared with an earlier reported member of the brevicidine family, the broadened antimicrobial spectrum of brevicidineB is caused by its increased membrane disruptive capacity on Gram-positive pathogens, which was evidenced by fluorescence microscopy assays. In addition, DiSC3(5) and resazurin assays show that brevicidine and brevicidineB exert their antimicrobial activity against Gram-negative bacteria via disrupting the proton motive force of cells. Notably, as a brevicidine family member, brevicidineB also showed neither hemolytic activity nor cytotoxicity at a high concentration of 64 mg/L. This study provides a promising antibiotic candidate (brevicidineB) with a broad antimicrobial spectrum, and provides novel insights into the antimicrobial mode of action of brevicidines.